2022
DOI: 10.1111/psyp.14050
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the error‐related negativity and anxiety in children and adolescents: From a neural marker to a novel target for intervention

Abstract: The current review focuses on our work on the relationship between the error‐related negativity (i.e., ERN) and anxiety in children and adolescents. The ERN is an event‐related potential (ERP) that appears as a negative deflection in the ERP waveform when individuals make errors and has been found to be increased in anxious individuals. We, and others, have extended this work into developmental populations, finding that the ERN can be measured reliably in children and that the ERN is increased among clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 173 publications
0
15
0
Order By: Relevance
“…An improved understanding of these changes could inform neuroscientific models of adolescent anxiety symptom development. This is because the ERN relates to risk for anxiety disorders (Buzzell et al, 2021;Fox et al, 2021;Meyer, 2022;Moser et al, 2013), which tend to emerge across the adolescent window. Extant systems-neuroscience models relating the ERN to anxiety tend to assume age-related stability in the neural basis of the ERN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An improved understanding of these changes could inform neuroscientific models of adolescent anxiety symptom development. This is because the ERN relates to risk for anxiety disorders (Buzzell et al, 2021;Fox et al, 2021;Meyer, 2022;Moser et al, 2013), which tend to emerge across the adolescent window. Extant systems-neuroscience models relating the ERN to anxiety tend to assume age-related stability in the neural basis of the ERN.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying age-related differences in neural circuits involved in error monitoring will deepen our knowledge of typical cognitive neurodevelopment and inform studies of atypical developmental patterns. In particular, the ERN has been identified as a predictor of increased anxiety risk across development (Fox et al, 2022;Meyer, 2017Meyer, , 2022. The investigation of brain functional responses would improve models of performance monitoring and inform future studies aiming to characterize the relationship between psychopathology and error monitoring systems.…”
Section: Introductionmentioning
confidence: 99%
“…Given our cross-sectional study design, it remains unknown whether the association between FNE and ERN remains stable across development. Emerging developmental theory on the nature of anxiety-ERN relations argues that whereas the ERNanxiety link in childhood is primarily driven by external threats/fears, ERN-anxiety relations fundamentally change with the transition to adolescence-to self-conscious shyness and worry about behavioral competence and social evaluation (Meyer, 2017(Meyer, , 2022. Meyer et al have shown that adolescent ERN-anxiety relations are primarily driven by social anxiety symptoms, as opposed to symptoms of other anxiety disorders (Meyer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work demonstrates that the ERN, an event-related potential (ERP) elicited by errors of commission (Falkenstein, Hohnsbein, Hoormann, & Blanke, 1991; Gehring, Goss, Coles, Meyer, & Donchin, 1993), can serve as a neural marker of exaggerated error monitoring (self-monitoring) in individuals with general anxiety (Hajcak, Klawohn, & Meyer, 2019; Meyer, 2022; Moser, Moran, Schroder, Donnellan, & Yeung, 2013; Olvet & Hajcak, 2008) and social anxiety (Endrass, Riesel, Kathmann, & Buhlmann, 2014; Kujawa et al, 2016; Meyer, Carlton, Crisler, & Kallen, 2018). Moreover, the ERN predicts a pattern of error-related autonomic responses that are typically observed in response to threat (Hajcak et al, 2003; Hajcak & Foti, 2008).…”
mentioning
confidence: 99%
“…Evidence indicates that standard treatment approaches, such as cognitive behavioral therapy, do not affect the ERN and performance-related worry (e.g., Ladouceur et al, 2018 , Riesel et al, 2015a ), suggesting that the increase in ERN amplitude and possibly the heightened perceived aversiveness of errors persist. Therefore, standard treatment approaches could be complemented by novel intervention strategies that directly target the ERN and may thereby reduce obsessive-compulsive or anxiety symptoms and/or the risk of developing such psychopathology ( Hajcak et al, 2019 , Klawohn et al, 2020a , Meyer, 2022 ). Even beyond putative effects on symptoms of psychopathology, modulation of aberrant error monitoring is informative for a better understanding of pathomechanisms and the identification of potential targets for psychophysiological intervention strategies.…”
Section: Introductionmentioning
confidence: 99%